Children as change agents in creating peer awareness for ear health - Rekha Sonavane; Deepthi R; Rashmi Rodrigues; Chikkaraju; Rathna Kumari (Al Ameen Medical College, 2012)
Background: Prevalence of ear health problems is common among school children. Students have the potential for changing the health scenario of the society if properly groomed and educated for healthful living. Several innovative approaches for health education like child to child programme have been tried in various health related situations to gain interest, support, involvement and commitment of students. Objectives: To evaluate the impact of health education in improving the knowledge of school children regarding ear health and to compare the effect of the Child to Child approach for health education with the Adult to Child approach. Methods: 212 students from the 2 classes were randomly divided into 2 groups. 4 children were trained to provide health education.105 students were educated using the child to child approach of health education while 107 were educated using the adult to child approach. Knowledge was tested pre and post intervention using a pretested closed ended questionnaire. Results: The overall pretest mean score of 4.91±1.29 increased significantly after health education to a mean posttest score of 6.89±1.84 (p<0.001). A significant improvement in mean scores after the health education within both the groups was seen (Child to child 4.94±1.29 Vs 7.01±1.85, Adult to child 2: 4.89±1.30 Vs 6.76±1.83, p<0.001). Mean pretest and post test scores of the two groups were similar. Conclusion: The study showed that children are as effective as adults for the dissemination of knowledge to other children and can be effective change agents in ear health.